Reduced prevalence of phage defense systems in Pseudomonas aeruginosa strains from cystic fibrosis patients - Daan F. van den Berg; Stan J. J. Brouns (mBio)
ABSTRACT Cystic fibrosis is a genetic disorder that affects mucus clearance, particularly of the lungs. As a result, cystic fibrosis patients often experience infections from bacteria, which contribute to the disease progression. Pseudomonas aeruginosa is one of the most common opportunistic pathogens associated with cystic fibrosis. The presence of P. aeruginosa complicates the treatment due to its high antibiotic resistance. Thus, research is ongoing to treat these infections with bacterial viruses instead, known as bacteriophages. Notably, P. aeruginosa clinical strains possess a variety of phage defense mechanisms that may limit the effectiveness of phage therapy. In this study, we compared the defense system repertoire of P. aeruginosa strains isolated from cystic fibrosis patients with those from non-cystic fibrosis patients. Our findings reveal that P. aeruginosa strains isolated from cystic fibrosis patients have fewer phage defense mechanisms per strain than from non-cystic fibrosis patients, suggesting altered phage selection pressures in strains colonizing CF patient lungs.IMPORTANCECystic fibrosis patients often experience chronic Pseudomonas aeruginosa lung infections, which are challenging to treat with antibiotics and contribute to disease progression and eventual respiratory failure. Phage therapy is being explored as an alternative treatment strategy for these infections. However, assessing strain susceptibility to phage treatment is essential for ensuring efficacy. To address this, we investigated whether CF-associated clinical P. aeruginosa strains have a distinct phage defense repertoire compared with those isolated from other lung patients. We observed that CF-associated P. aeruginosa strains have significantly fewer phage defenses, possibly affecting the susceptibility of these strains to phage infection.